Rajskie są okolice Cieszyna, czyli jak dr František Sláma cieszyńskich Cyganów sądził - Spyra, Janusz (Studia Etnologiczne i Antropologiczne, 2011)
The article discusses literary works by František Sláma (1850—1917), a Czech national activist, writer and columnist working as a judge of the district court in Cieszyn between 1882 and 1888, devoted to gypsies (the Romany people). It covers four short stories created at this time and reprinted several times also translated into Slovak and the article devoted to Gypsies in Cieszyn Silesia. The leading themes of subsequent stories are baptism, wedding, confession and love between a young gypsy girls and a young non-gypsy boy. In the last one the author used a real event though it is above all based on the knowledge he had thanks to his contacts with gypsies as a judge. However, he colours his plot with motives taken from different sources. The author bases on a fairly stereotyped vision of the Romany life, the basis of which is to include petty thefts as a result of which they are constantly tried and from which they try to free themselves through lies, excuses or, “gypsying” Sláma wrote about gypsies in the article (“On gypsies in Cieszyn”) published in the magazine “Slovansky sbornik” in 1887. Both in the article and short stories Sláma presents the Romany people with friendliness, through which he shapes their image, perhaps negative, but familiar.